2012
DOI: 10.1172/jci64617
|View full text |Cite
|
Sign up to set email alerts
|

Treg-mediated suppression of atherosclerosis requires MYD88 signaling in DCs

Abstract: TLR activation on CD11c + DCs triggers DC maturation, which is critical for T cell activation. Given the expansion of CD11c + DCs during the progression of atherosclerosis and the key role of T cell activation in atherogenesis, we sought to understand the role of TLR signaling in CD11c + DCs in atherosclerosis. To this end, we used a mouse model in which a key TLR adaptor involved in DC maturation, MYD88, is deleted in CD11c + DCs. We transplanted bone marrow containing Myd88-deficient CD11c + DCs into Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(151 citation statements)
references
References 61 publications
6
142
1
2
Order By: Relevance
“…[25][26][27][28] Initial studies 1,29,30 indicated the atheroprotective potential of the B-cell compartment that relies on B1a cells and germ-line-encoded immunoglobulins. In contrast, recent studies have identified T-dependent B cells (B2 cells) as potent proatherogenic mediators in the ApoE° and low-density lipoprotein receptor-knockout mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Initial studies 1,29,30 indicated the atheroprotective potential of the B-cell compartment that relies on B1a cells and germ-line-encoded immunoglobulins. In contrast, recent studies have identified T-dependent B cells (B2 cells) as potent proatherogenic mediators in the ApoE° and low-density lipoprotein receptor-knockout mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentation was carried out as previously described by our laboratory (10,72). In brief, aortic root sections were stained with TUNEL (Roche) followed by Mac-3 (BD BiosciencesPharmingen) to label lesional macrophages.…”
Section: Mice Ldlrmentioning
confidence: 99%
“…Aortic root lesional material from 5 mice was captured (twelve 5-μm sections per mouse) using a PALM LCM microscope as previously described (72). RNA was isolated using the RNeasy Mini Kit (QIAGEN, catalog 74106) and linearly amplified using the Message Amp II aRNA Kit (Ambion, catalog AM1751).…”
Section: Mice Ldlrmentioning
confidence: 99%
“…Modified from reference 19) . + DCs is required for the differentiation of both effecter T cells and Treg cells, the net result in Ldlr −/− mice is the enhanced recruitment of monocytes to the plaque lesion due to the loss of the Treg-mediated suppression of MCP-1 68) . These results indicate that the role of TLR4 signaling in atherogenesis is likely to be ligand-, timing-and cell type-dependent.…”
Section: Tlr4 Signaling Under Conditions Of Insulin Resistance and Pamentioning
confidence: 99%